CHARACTERIZATION OF THE HOSPITALIZATION OF DRUG ADDICTS IN A REHABILITATION UNIT - Aline Cristina Zerwes Ferreira; Fernanda Carolina Capistrano; Mariluci Alves Maftum; Luciana Puchalski Kalinke; Ana Lúcia Cardoso Kirchhof (Universidade Federal do Paraná, 2012)
This cross-sectional, retrospective research used the technique of documental research. Its objective was to characterize the hospitalization of drug addicts in a rehabilitation unit. Data was collected from 350 patient records belonging to drug addicts, referring to 2010. Regarding the characterization of the subjects, the average age was 35.8 years, 39.4% were single, 67.3% had only studied at primary school level and 45.1% were unemployed. Alcohol was the motive for treatment in 45.1% of the patients; 49.4% were diagnosed as dependent on multiple drugs. Hospitalization was voluntary for 97.1%; 40.4% of those responsible were the parents; clinical discharge predominated in 55.4% and, after discharge, 86% were referred to community services. Among the participants, 71.7% had been hospitalized before and 29.9% had undertaken other types of treatment. The results demonstrate that to aim for permanent abstinence, it is essential to maintain treatment after the hospitalization.